2022
DOI: 10.1007/s11130-022-00959-2
|View full text |Cite
|
Sign up to set email alerts
|

Onion Vinegar Quality Evaluation and its Alleviate Oxidative Stress Mechanism in Caenorhabditis elegans Via SKN-1

Abstract: Recently, there has been renewed interest in biorefining of agricultural onion into functional products. In this study, onion vinegar (OV) are prepared by a two-stage semi-continuous fermentation method, and its content of total flavonoids (3.01 mg/mL) and polyphenols (976.76 μg/mL) is superior to other commercial vinegars. OV possesses a high radical scavenging activity and enhances the antioxidant enzyme activities in vivo, alleviating intracellular oxidative stress in Caenorhabditis elegans. Treated by OV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The antioxidative active factors upon exogenous stimulation of C. elegans was reported to reduce oxidative damage in vivo [ 5 ]. This motivated us to speculate whether D. officinale ACNs can also alleviate oxidative stress in C. elegans .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The antioxidative active factors upon exogenous stimulation of C. elegans was reported to reduce oxidative damage in vivo [ 5 ]. This motivated us to speculate whether D. officinale ACNs can also alleviate oxidative stress in C. elegans .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the SOD activity reached 1.3087 ± 0.4451 U/mg prot ( p < 0.05). SOD and CAT, two major antioxidant enzymes in C. elegans , have the main function of scavenging superoxide free radicals and H 2 O 2 [ 5 ]. The results indicated that the ACNs from D. officinale mainly increased the SOD activity, while the effect on CAT and GSH-Px activity was not obvious.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations